2012
DOI: 10.5606/kbbihtisas.2012.054
|View full text |Cite
|
Sign up to set email alerts
|

A case of an apocrine hidrocystoma treated by sublabial approach

Abstract: Apocrine hidrocystomas are uncommon cystic proliferations of the apocrine secretory glands. Maxilla is an unexpected involvement site for these tumors. Our study represents the first case of an apocrine hidrocystoma of the maxilla excised by an intraoral (sublabial) approach, being the first to define the radiologic findings of apocrine hidrocystoma on this region. This case is an extremely rare type in terms of the unusual symptomatology, location and size of the tumor. In this article, clinical presentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…14 These are asymptomatic lesions that localize especially in the periorbital area of the head and neck region. 14 In our study, AHC was identified in 1 case and the localization of the mass was periorbital, which was consistent with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…14 These are asymptomatic lesions that localize especially in the periorbital area of the head and neck region. 14 In our study, AHC was identified in 1 case and the localization of the mass was periorbital, which was consistent with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…AHC most commonly appears on the eyelid margins [12][13][14][15], oral mucosa [16,11,17] and ear [11,17,18]. We would like to report that both our cases of AHC, when compared to more classical presentations, do not have arborizing vessels, and has a less common location on the nasal ala, contributing to the literature of other variants, including eccrine [19] and planar AHC variants [20], reported on the nasal ala.…”
Section: Discussionmentioning
confidence: 66%
“…AHC tend to appear as a solitary, homogeneous papule or nodule, typically ranging in size from 3–15mm [ 10 ], either skin-colored or with pink, yellow or blue color hue, and can have secondary features such as arborizing vessels seen under dermoscopy [ 11 ]. AHC most commonly appears on the eyelid margins [ 12 – 15 ], oral mucosa [ 16 , 11 , 17 ] and ear [ 11 , 17 , 18 ]. We would like to report that both our cases of AHC, when compared to more classical presentations, do not have arborizing vessels, and has a less common location on the nasal ala, contributing to the literature of other variants, including eccrine [ 19 ] and planar AHC variants [ 20 ], reported on the nasal ala.…”
Section: Discussionmentioning
confidence: 99%